Tindakan Korektif Dan Preventif Kode Kegagalan 12 Pada Motor Yamaha Aerox Keluaran (2016-2019) : Studi Kasus Di Bengkel Yamaha Mattaram Sakti Serang - Fahri Aprianto; Ananda Yhuto Wibisono Putra (GLOBAL SCIENTS PUBLISHER, 2025)
Code 12 on the first 2016-2019 Yamaha Aerox motorbike could indicate a problem with the throttle position sensor or the cables connected to it. If the code 12 condition continues to flash without being addressed, engine performance problems will arise which can affect throttle response and fuel efficiency. The research was carried out at the Yamaha Mataram Sakti Serang Dealer workshop with the aim of taking corrective action on the causes of the frequent appearance of code 12 on Yamaha Aerox motorbikes released in the 2016-2019 edition. The research method uses qualitative research with a case study type of research. The results and discussion show data that the diagnosis of code 12 and the corrective action taken can be in the form of a jump start technique on cables without sockets to normalize currents whose distribution is unbalanced. Meanwhile, the preventive action that must be taken is to pay attention to the magnetic current on the spool and socket cable so as not to trigger error code 12 by means of regular maintenance and service on the spool and socket. However, code 12 that appears on 2016-2019 Yamaha Aerox motorbikes and is left untreated will result in further damage to engine performance. Keywords: Code 12; Corrective action; Sensors Yamaha Aerox